Gendered oppression and textual power: A critical discourse analysis of online gender-based violence in the RK case on IDNTimes.com - Shifa Putri Agdelia; Ayu Kartika (Digital Theory, Culture & Society, 2025)
This study addresses the increasing prevalence of Online Gender-Based Violence (OGBV) in Indonesia, which continues to affect both women and men, although women remain the most vulnerable and disproportionately impacted. Focusing on the case of RK, a public figure whose explicit videos with her former partner were circulated online, this research highlights not only the fragility of privacy and consent in the digital era but also the ideological mechanisms maintained through the media’s framing and textual production. The study aims to analyze how media representation shapes public perception, moral judgment, and emotional engagement with RK’s case. Employing a qualitative approach and Sara Mills’ Critical Discourse Analysis framework, it examines multiple articles from *Idntimes.com* to uncover linguistic strategies, power relations, and gendered ideologies embedded in the narratives. The findings reveal consistent portrayals of RK as a passive, powerless, and morally suspect victim, reinforcing a culture of victim-blaming while simultaneously evoking limited empathy. These media constructions mirror broader social, cultural, and structural inequalities in Indonesia’s treatment of women involved in sexual scandals. Ultimately, this study calls for more ethical and gender-sensitive media practices that amplify victims’ voices and promote empathetic, equitable, and socially conscious public discourse on sexual violence.